2021
DOI: 10.1111/joca.12362
|View full text |Cite
|
Sign up to set email alerts
|

The role of vending channels in marketing: A systematic review and taxonomy of studies

Abstract: Although vending machines emerged centuries ago, only recently have they regained popularity. This study aims to provide a systematic review of available marketing literature on food and drink vending channels to delineate under‐researched marketing areas that require further investigation. Therefore, the abstracts of 2,409 articles were manually screened, of which 98 were retained as the most relevant for further synthesis. The author organized the existing marketing literature from a consumer point of view a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Considering that vending retail marketing is an emerging research field (Stoyanov, 2021а, b), we adopted an inductive approach for theory building to select the independent variables for our experimental design, that involved conducting a focus group interview with six managers in different positions in the vending industry to identify the marketing mix elements perceived as the main sources of future competitive advantage in the industry. The results revealed product quality, payment system and internal location as the primary sources of future competitive advantage (see Appendix).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that vending retail marketing is an emerging research field (Stoyanov, 2021а, b), we adopted an inductive approach for theory building to select the independent variables for our experimental design, that involved conducting a focus group interview with six managers in different positions in the vending industry to identify the marketing mix elements perceived as the main sources of future competitive advantage in the industry. The results revealed product quality, payment system and internal location as the primary sources of future competitive advantage (see Appendix).…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review revealed that, over the last 20 years, vending retail channels were studied extensively from a social standpoint (to improve health and nutrition in schools and universities) but their retail marketing aspects have been long neglected (Stoyanov, 2021b). Additionally, some studies have been dedicated to inventory management and industrial engineering (Grzybowska et al, 2020).…”
Section: Vending Retail Marketingmentioning
confidence: 99%
See 2 more Smart Citations
“…The core distinction lies in that (1) traditional attended retail stores totally rely on the operation and management of in-store personnel to deal with consumer inquiries and checkout and that (2) digitally transformed/developed retail stores are only an upgraded version of the former through adopting e-service touchpoints (Barann et al, 2022 ) or implementing partial technological solutions reducing, rather than replacing, manual operation, including retail information systems (e.g., inventory management, retail enterprise resource planning), self-service checkouts, and mobile payments; in other words, digitally transformed retail stores still largely provide a staffed shopping environment for customers. Additionally, smart retail stores do not encompass vending machines alike self-service business models that do not offer an immersive in-store shopping environment with various embedded smart technologies (Stoyanov, 2021 ). Apparently, the “brick and mortar” nature also distinguishes smart retail stores from online retailers, which can never fulfill consumers’ need for a tactile retail experience.…”
Section: Literature Reviewmentioning
confidence: 99%